Oral Microbiome Transplantation: A Novel Therapeutic Approach for Restoring Oral and Systemic Health - Krishna, Ambati Vamsi; Bharathy, Kommaraju Sree Vijaya; Chakravarthy, Adusumalli (Indian Journal of Pharmacy Practice)
Oral Microbiome Transplantation (OMT) is a novel therapeutic strategy designed to restore microbial equilibrium in the oral cavity to address diseases linked to oral dysbiosis, such as dental caries and periodontitis, as well as associated systemic conditions like diabetes and cardiovascular disease. In contrast to traditional therapies that mostly focus on alleviating symptoms by mechanical plaque removal or restoration procedures, OMT aims to rectify the root problem by reinstalling advantageous microorganisms from healthy donors into the oral ecosystem. This work investigated the feasibility and potential of OMT using an innovative hydrogel-based delivery method made from dopamine-grafted oxidized sodium alginate, aimed at improving microbial viability and ensuring steady application. The hydrogel exhibited advantageous characteristics, such as mechanical stability, biocompatibility, and the capacity to maintain microbial functioning, making it a suitable medium for microbial transfer. A major problem in OMT is the identification of appropriate donors, attributed to the interpersonal variability of oral microbiota; the notion of a “super donor” with a highly diversified, stable, and low-pathogenic microbiome is highlighted as crucial for therapeutic effectiveness. Initial findings from canine models indicated that OMT decreased inflammation and obstructed the development of pathogenic biofilms, corroborating its efficacy as both a therapeutic and preventative intervention. Nonetheless, more study is necessary to convert these discoveries into human applications, including thorough safety evaluations, rigorous donor screening procedures, and extensive investigations to assess the longevity and integration of transplanted microbiota. If proven, OMT might signify a transformative change in dental care, providing a comprehensive, root-cause-oriented alternative to traditional therapies for oral and systemic health management.
Keywords: Oral microbiome; Microbiome transplantation; Oral dysbiosis; Periodontitis; Dental caries; Super donor; Hydrogel delivery system; Oral health; Systemic disease